SOUTH KOREAN LEADERS IN THE POLITICS OF DEMOCRATIZATION - STRNAD, Grażyna (International Journal of Korean Humanities and Social Sciences, 2017)
This article aims to show the process of formation and operation (functioning) of the changing political system of South Korea. It is undertaken for the analysis of the process of the collapse of the former authoritarian political system and formation of South Korean democracy. Indicated in this article are the roles and participation of political leaders (Chun Doo Hwan, Roh Tae Woo, Kim Young Sam, and Kim Dae Jung) in the process of intense political change that took place in South Korea from the 1980s to the late twentieth century. During the authoritarian regimes of South Korea, the nation recorded spectacular economic development, but without political development. Political leadership in the democratization of the country was still authoritarian. Core values and attitudes of politicians pointed to the presence of the cultural heritage of Confucianism in politics.